Herramientas de software para la planificación y control de proyectos de investigación-desarrollo en la U.N.L. - Ruiz Vivanco, Omar Alexander (2008)
The software tool designed for Planning and Control Research Projects - Development, is the result of an investigation of software engineering in the analysis and design of a framed within the technical, economic and social feasibilities solution that fit the reality of AEIRNNR, and ordering information project management undergraduate and graduate thesis, formative research projects and technological research projects, meeting the main objective of this research work. The software "pcpweb" as it has been called by its author, is designed as a web application in three layers (presentation, application and data) using Java Server Pages (JSP) technology based on the Java language, combining HTML tags special and fragments of Java code allowing incorporate dynamic content to web pages, MySQL, relational database archiving data generated in the system, receiving requests for storage or retrieval of information, Tomcat, also called Jakarta Tomcat or Apache Tomcat, web server with support servlets and JSPs.   Analyzing the specific objectives mentioned that the system introduces a control methodology different projects, it generates the respective in each of its phases reports and has become the author on the basis of professional experience proving its work in the competitive working world.